Estimation of the potential geographical distribution of invasive peach fruit fly under climate change by integrated ecological niche models - Farman Ullah; Yuan Zhang; Hina Gul; Muhammad Hafeez; Nicolas Desneux; Yujia Qin; Zhihong Li (CABI Agriculture and Bioscience)
Abstract Climate change and biological invasions of insect pests are interlinked global concerns that drive shifts in the distribution of invasive insects. The peach fruit fly, Bactrocera zonata Saunders, is one of the most economically important Tephritidae species that attack several host plants and causes serious damage in Asia and Africa. Currently, B. zonata is absent from many countries and regions but has a risk of invasion. Therefore, it is crucial to investigate the impact of climate change on the global potential distribution of B. zonata. In this study, we used MaxEnt and CLIMEX models to estimate the risk area for B. zonata under near current and future climate conditions. The MaxEnt and CLIMEX results showed that the south of North and Central America was suitable for B. zonata. The European countries were slightly suitable for B. zonata. In Asia, the highly suitable regions of B. zonata included Saudi Arabia, United Arab Emirates, Oman, Iran, Pakistan, India, Nepal, Bangladesh, Bhutan, Myanmar, Thailand, Vietnam, and Laos. Moreover, China, Philippines, Indonesia, and Japan showed highly climate suitability for B. zonata. The climate suitability of B. zonata was increasingly high in the projection under climate change. The result of the two models showed that the climatic suitability for B. zonata will increase under climate change in China. Taken together, these predictive results support the quarantine of B. zonata for high-risk countries and provide in-depth information on how climatic changes may affect its possible geographic range.